KEBIJAKAN INVESTASI DALAM KAITANNYA DENGAN PEMBANGUNAN INDUSTRI YANG BERWAWASAN LINGKUNGAN - Alit Pratiwi, Ni Nyoman; Rai Setiabudhi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
This article discusses the increasingly rapid growth of investment in Indonesia,both domestic investors and foreign investors are characterized as more establishedcompanies, especially big companies in the industry that would have to consider thecondition of the surrounding environment from being damaged or contaminated. Thegoals to be achieved in the writing of this paper is to determine whether the existinginvestment policy has been to support the development of environmentally soundindustry. The research method used is normative research. The results of the researchconducted it can be seen that the existing investment policy has yet to fully support theimplementation of the investment in relation to the construction industry. Investmentpolicy that has been made by the government not provide strict sanctions againstbusinesses that conduct investment activities but then pollute the surroundingenvironment.
Keywords: investment, development, industry, environment